Sequence Analysis of the Dimerization Initiation Site of Concordant and Discordant Viral Variants Superinfecting HIV Type 1 Patients - Mayr, Luzia (Mary Ann Liebert, Inc., 2011)
For HIV recombination to occur, the RNAs from two infecting strains within a cell must dimerize at the dimerization initiation site (DIS). We examined the sequence identity at the DIS (697–731 bp, Hxb2 numbering engine) in patients superinfected with concordant HIV-1 strains and compared them to those with discordant strains. Viral RNA in sequential plasma from four subjects superinfected with subtype-discordant and two subjects superinfected with subtype-concordant HIV-1 strains was extracted, amplified (5′ LTR-early gag: 526–1200 bp, Hxb2 numbering engine), sequenced, and analyzed to determine their compatibility for dimerization in vivo. The concordant viruses infecting the two subjects exhibited identical sequences in the 35-bp-long DIS region while sequences from the discordant viruses revealed single nucleotide changes that were located in the DIS loop (715 bp), its flanking nucleotides (710 bp and 717 bp), and the DIS stem (719 bp). Evidence from in vitro experiments demonstrates that these in vivo changes identified can abolish dimerization and reduce recombination frequency. Therefore, these results revealing differences in the DIS of discordant strains versus the similarity noted for the concordant strains may contribute to the differences in the frequency of recombination in patients superinfected with such HIV-1 variants.